A discussion of blood cancers and the MPN landmark survey. (December 2017) - Harrison, Claire
Professor Claire Harrison speaks to Roshaine Wijayatunga, managing commissioning editor: Professor Claire Harrison became a consultant at Guy's and St Thomas' hospital in 2001. She is also deputy clinical director of cancer and hematology. She has influenced major advances in her field, including the description of key mutations and designing/leading global clinical trials, for example, the first JAK inhibitor trial in Europe. She is the chief investigator for several other international and national clinical trials. She has strong international collaborations and authors many papers in peer-reviewed journals such as the New England Journal of Medicine and Blood . She has worked with enthusiastic patients to create a patient charity, MPN Voice. She is an internationally regarded expert in her field as a patient advocate.